Supramolecular architecture based on the self-assembling of multiwall carbon nanotubes dispersed in polyhistidine and glucose oxidase: Characterization and analytical applications for glucose biosensing - Dalmasso, Pablo Roberto (2012)
We report for the first time the development of a sensitive and selective glucose biosensor based on the self-assembling of multiwall carbon nanotubes (MWCNTs) dispersed in polyhistidine (Polyhis) and glucose oxidase (GOx) on glassy carbon electrodes (GCE). The supramolecular architecture was characterized by SEM, FT-IR and electrochemical techniques. The optimum multistructure was obtained with five (MWCNT-Polyhis/GOx) bilayers and one layer of Nafion as anti-interferent barrier. The sensitivity at 0.700 V was (1.9470.03) mA M1 (r¼0.9991), with a linear range between 0.25 and 5.00 mM, a detection limit of 2.2 mM and a quantification limit of 6.7 mM with minimum interference from lactose (1.5%), maltose (5.7%), galactose (1.2%), ascorbic acid (1.0%), and uric acid (3.3%). The biocatalytic layer demonstrated to be highly reproducible since the R.S.D. for 10 successive amperometric calibrations using the same surface was 3.6%. The sensitivity of the biosensor after 15 day storage at 4 1C remained at 90% of its original value. The combination of the excellent dispersing properties and polycationic nature of polyhistidine, the stability of the MWCNT-Polyhis dispersion, the electrocatalytic properties of MWCNTs, the biocatalytic specificity of GOx, and the permselective properties of Nafion have allowed building up a sensitive, selective, robust, reproducible and stable glucose amperometric biosensor for the quantification of glucose in milk samples.